english: english - Nabilah Farah Fadilah; Fuad Ardiansyah; Putrawansyah Putrawansyah (CV. AFDIFAL MAJU BERKAH, 2026)
This study investigated the effectiveness of Universal Picture Card Media (UPCM) in enhancing elementary school students’ public speaking skills through a quasi-experimental pretest–posttest design. The participants consisted of 20 students aged 10–12 years from SD Muhammadiyah 2 Sorong City, selected using purposive sampling and divided equally into experimental and control groups. Students’ speaking performance was assessed based on six indicators: pronunciation accuracy, fluency, grammatical accuracy, coherence and cohesion, clarity of message delivery, and confidence in social interaction. Data were collected through structured speaking tests, classroom observations, and documentation, and analyzed using descriptive statistics and the nonparametric Mann–Whitney U test due to non-normal data distribution in one dataset. The results revealed a statistically significant difference between the experimental and control groups (U = 0.000; Z = −3.791; p < 0.05). The experimental group’s mean score increased substantially from 21.70 in the pretest to 48.50 in the posttest, representing a 26.80% improvement. In contrast, the control group showed only a marginal increase from 23.00 to 24.40. The most notable improvement in the experimental group was observed in fluency (M = 4.40) and confidence and social interaction (M = 4.40), while coherence and cohesion demonstrated the greatest developmental progression across cycles. Pronunciation accuracy showed improvement but remained the lowest indicator compared to others. The intervention was implemented over three cycles and three meetings, integrating storytelling, singing activities, educational games, and structured debriefing sessions. These findings demonstrate that UPCM provides effective visual scaffolding that significantly enhances students’ structured expression, fluency, and communicative confidence in public speaking contexts.